(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
An inclement dusty weather can significantly reduce the visual quality of captured images, which consequently hampers the observation of important image details. Capturing images in such weather often yields undesirable artifacts such as poor contrast, deficient colors or color cast. Hence, various methods have been proposed to process such unwanted events and recover lucid results with acceptable colors. These methods vary from simple to complex due to the variation of the used processing concepts. In this article, an innovative technique that utilizes tuned fuzzy intensification (FI) operators is introduced to expeditiously process poor quality images captured in an inclement dusty weather. Intensive experiments were carried out to check the processing ability of the proposed technique, wherein the obtained results exhibited its competence in filtering various degraded images. Specifically, it performed well in providing acceptable colors and unveiling fine details for the processed images.